Reduce unemployment rate and increase economic growth: case at north maluku - Muhsin Bailusy; Prince Charles Heston Runtunuwu; Sulfi Haji (Jurnal Mantik, 2023)
The purpose of this study is to analyze the financial performance of the Tidore Islands government, how the influence of the government's financial performance on economic growth and the open unemployment rate in the Tidore Islands City. The data used in the analysis is quantitative data sourced from: reports on the realization of the Regional Revenue and Expenditure Budget (APBD), Economic Growth and data on the Open Unemployment Rate of Tidore Archipelago City. All secondary data is sourced from the Regional Development Planning Agency (Bappeda), the Central Statistics Agency (BPS), as well as reports related to this research. The data in this study are time series in 2013-2020 and use path analysis. The variables observed in this study include regional financial performance, economic growth and unemployment. The results showed that the local government's financial performance which consisted of independence, efficiency, effectiveness and suitability of spending had an effect on economic growth. Financial performance also has an effect on reducing the open unemployment rate in the Tidore Archipelago City. Economic growth has an effect on the open unemployment rate in the Tidore Archipelago City. That is, the better the economic growth, the lower the open unemployment rate in the Tidore Archipelago City